Matrix metalloproteinase‐9 gene polymorphisms are associated with ischemic stroke severity and early neurologic deterioration in patients with atrial fibrillation. Issue 6 (22nd April 2019) - Yi, Xingyang; Zhou, Qiang; Sui, Guo; Fan, Daofeng; Zhang, Yongyin; Shao, Minjie; Han, Zhao; Luo, Hua; Lin, Jing; Zhou, Ju
Abstract: Objectives: The mechanisms of ischemic stroke severity and early neurologic deterioration (END) are not fully understood. The aim of the present study was to investigate the association of six variants in MMP‐9 gene with ischemic stroke severity and the risk for END in ischemic stroke (IS) patients with atrial fibrillation (AF). Methods: This was a multi‐center, prospective, observational study of 615 acute IS patients with AF admitted to six participating hospitals between June 2016 and October 2017. Ischemic stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) score on admission. END was defined as an increase of four or more points in NIHSS within 10 days of admission. Six variants of MMP‐9 gene were examined using mass spectrometry. Results: Among the 615 enrolled patients, 112 (18.2%) patients presented with moderate or severe stroke (NIHSS score ≥16), and 108 (17.6%) patients suffered from END within 10 days of admission. Multiple logistic analysis showed that prestroke antiplatelet therapy, prestroke anticoagulant therapy, rs3918242 CT/TT, and rs3787268 AG/GG were independent predictors for stroke severity. Cox proportional hazard regression revealed that diabetes mellitus, prestroke antiplatelet therapy, prestroke anticoagulant therapy, rs1056628 AC/CC, and rs3918242 CT/TT were independently associated with the risk of END. Conclusions: The incidence of moderate or severe stroke and END was very common in acute IS patients with AF. MMP‐9 polymorphisms were independently associated with severe stroke and higher risk of END, and prestroke antithrombotic treatment was associated with less severe stroke and lower risk of END in patients with AF. Abstract : The mechanisms of ischemic stroke severity and early neurologic deterioration (END) are not fully understood in ischemic stroke (IS) patients with atrial fibrillation (AF). The incidence of moderate or severe stroke and END was very common in acute IS patients with AF. MMP‐9 polymorphisms were independently associated with severe stroke and higher risk of END, and prestroke antithrombotic treatment was associated with less severe stroke and lower risk of END in patients with AF.